Mapping H4K20me3 onto the chromatin landscape of senescent cells indicates a function in control of cell senescence and tumor suppression through preservation of genetic and epigenetic stability. Issue 1 (December 2016) - Nelson, David; Jaber-Hijazi, Farah; Cole, John; Robertson, Neil; Pawlikowski, Jeffrey; Norris, Kevin; Criscione, Steven; Pchelintsev, Nikolay; Piscitello, Desiree; Stong, Nicholas; Rai, Taranjit; McBryan, Tony; et al.
Abstract Background Histone modification H4K20me3 and its methyltransferase SUV420H2 have been implicated in suppression of tumorigenesis. The underlying mechanism is unclear, although H4K20me3 abundance increases during cellular senescence, a stable proliferation arrest and tumor suppressor process, triggered by diverse molecular cues, including activated oncogenes. Here, we investigate the function of H4K20me3 in senescence and tumor suppression. Results Using immunofluorescence and ChIP-seq we determine the distribution of H4K20me3 in proliferating and senescent human cells. Altered H4K20me3 in senescence is coupled to H4K16ac and DNA methylation changes in senescence. In senescent cells, H4K20me3 is especially enriched at DNA sequences contained within specialized domains of senescence-associated heterochromatin foci (SAHF), as well as specific families of non-genic and genic repeats. Altered H4K20me3 does not correlate strongly with changes in gene expression between proliferating and senescent cells; however, in senescent cells, but not proliferating cells, H4K20me3 enrichment at gene bodies correlates inversely with gene expression, reflectingde novo accumulation of H4K20me3 at repressed genes in senescent cells, including at genes also repressed in proliferating cells. Although elevated SUV420H2 upregulates H4K20me3, this does not accelerate senescence of primary human cells. However, elevated SUV420H2/H4K20me3 reinforces oncogene-induced senescence-associated proliferation arrest and slows tumorigenesis in vivo. Conclusions These results corroborate a role for chromatin in underpinning the senescence phenotype but do not support a major role for H4K20me3 in initiation of senescence. Rather, we speculate that H4K20me3 plays a role in heterochromatinization and stabilization of the epigenome and genome of pre-malignant, oncogene-expressing senescent cells, thereby suppressing epigenetic and genetic instability and contributing to long-term senescence-mediated tumor suppression.